2011
DOI: 10.1155/2011/719059
|View full text |Cite
|
Sign up to set email alerts
|

Endometriosis Gene Expression Heterogeneity and Biosignature: A Phylogenetic Analysis

Abstract: Endometriosis is a multifactorial disease with poorly understood etiology, and reflecting an evolutionary nature where genetic alterations accumulate throughout pathogenesis. Our objective was to characterize the heterogeneous pathological process using parsimony phylogenetics. Gene expression microarray data of ovarian endometriosis obtained from NCBI database were polarized and coded into derived (abnormal) and ancestral (normal) states. Such alterations are referred to as synapomorphies in a phylogenetic se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…This showed the potential pathologic roles of eutopic endometrium in endometriosis . The differential gene expressions are probably dedicated to primary disorders residing in the eutopic endometrium, which suggests that this novel signal, TF/PAR‐2 may be involved in the initial phase of endometriosis.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…This showed the potential pathologic roles of eutopic endometrium in endometriosis . The differential gene expressions are probably dedicated to primary disorders residing in the eutopic endometrium, which suggests that this novel signal, TF/PAR‐2 may be involved in the initial phase of endometriosis.…”
Section: Discussionmentioning
confidence: 85%
“…The co‐upregulated expression of TF and PAR‐2 in secretory phase in eutopic endometrium seems to plan the next menstrual cycle, potentially predisposing to survival and implantation of retrograde menstruated endometrial cells in the abdominal cavity . This showed the potential pathologic roles of eutopic endometrium in endometriosis . The differential gene expressions are probably dedicated to primary disorders residing in the eutopic endometrium, which suggests that this novel signal, TF/PAR‐2 may be involved in the initial phase of endometriosis.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the gynecologic system, TNS1 is involved in implantation and oogenesis, and is expressed in the endometrium . A phylogenetic study of ovarian endometriosis revealed that TNS1 is overexpressed in endometriotic tissue compared with eutopic tissues . However, no reports to date have described the effect of hormonal treatment on TNS1 expression in women with endometriosis.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, these treatments are not curative and have high associated side effects and remission rates 1,2 . While targeted therapies are urgently needed, their development has been hindered by the heterogeneity 3,4 and limited mechanistic understanding of the disease. Based on the widely accepted Sampson's theory, endometriosis arises when tissue fragments shed during menstruation implant in the surrounding tissue 5 .…”
Section: Introductionmentioning
confidence: 99%